Measurement of Apelin as a Biomarker and Its Relationship to Cystatin C, Copeptin, and Glomerular Filtration Rate in Serum of Patients with Acute Kidney Injury in Mosul City, Iraq - Anwar S. Majeed; Layla A. Mustafa (Medical Journal of Babylon)
Background: There is a need for early and accurate diagnosis of acute kidney injury, as high levels of cystatin C, copeptin, and low apelin levels in serum can provide an early diagnosis of acute kidney injury in patients. Objectives: To measure the level of apelin as a biomarker in the blood serum of both control and acute kidney injury groups, and to find its relationship with each of cystatin C, copeptin, and estimated glomerular filtration rate of both groups. Materials and Methods: This study was conducted on 232 blood samples collected from males and females, 108 from control subjects and 124 from patients with acute kidney injury, aged between 35 and 56 years. Results: Serum apelin (pg/mL) levels decreased in the blood serum of the acute kidney injury patients group, increased both cystatin C and copeptin, and decreased estimated glomerular filtration rate compared to the control group. Conclusion: The results showed that serum apelin levels decreased in the blood serum of the acute kidney injury group, corresponding to an increase in the level of both cystatin C and copeptin levels and a decrease in the estimated glomerular filtration rate compared to the control group, which indicates the possibility that apelin is a strong predictive biomarker for acute kidney injury, and it can play a good preventive and therapeutic role in the future.